2021
DOI: 10.1186/s12884-021-04173-x
|View full text |Cite
|
Sign up to set email alerts
|

Rates and indications of caesarean section deliveries in Bhutan 2015–2019: a national review

Abstract: Background Bhutan has made much efforts to provide timely access to health services during pregnancy and increase institutional deliveries. However, as specialist obstetric services became available in seven hospitals in the country, there has been a steady increase in the rates of caesarean deliveries. This article describes the national rates and indications of caesarean section deliveries in Bhutan. Methods This is a review of hospital records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It must also be noted that bypassing the referral system may be counterproductive in terms of patient outcomes. For example, all institutional deliveries in Bhutan are attended by skilled professionals—health assistants, midwives and doctors at the primary and second‐tier hospitals, and by obstetricians at the seven obstetric centres [18]. Many women with no high‐risk pregnancy bypass the referral channel and present to these obstetric centres for delivery.…”
Section: How Robust Is the Gatekeeping Function Of The Referral Pathw...mentioning
confidence: 99%
See 1 more Smart Citation
“…It must also be noted that bypassing the referral system may be counterproductive in terms of patient outcomes. For example, all institutional deliveries in Bhutan are attended by skilled professionals—health assistants, midwives and doctors at the primary and second‐tier hospitals, and by obstetricians at the seven obstetric centres [18]. Many women with no high‐risk pregnancy bypass the referral channel and present to these obstetric centres for delivery.…”
Section: How Robust Is the Gatekeeping Function Of The Referral Pathw...mentioning
confidence: 99%
“…In the absence of national standards and guidelines on making decisions on caesarean deliveries, these women end up with more likelihood of delivering babies by caesarean section at centres where an obstetrician is available. Bhutan has an increasing rate of caesarean deliveries which may be counterproductive towards the 2030 Sustainable Development Goal agenda [18].…”
Section: How Robust Is the Gatekeeping Function Of The Referral Pathw...mentioning
confidence: 99%
“…In Bhutan, the rate of cesarean section (CS) is around 18.7%. 3 The most common indications for CS were previous CS, fetal distress, prolonged labor, and failed induction. 3 Complications of cesarean delivery can be immediate and late with commonest complication being postpartum hemorrhage, sepsis, and wound infection.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The most common indications for CS were previous CS, fetal distress, prolonged labor, and failed induction. 3 Complications of cesarean delivery can be immediate and late with commonest complication being postpartum hemorrhage, sepsis, and wound infection. 1 , 4 Uterine scar dehiscence following lower segment cesarean section (LSCS) is rare with incidence of 0.6%.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Cesarean delivery rates are increasing worldwide. [7][8][9][10][11] Published data from 154 countries covering 94.5% of the world's live births found that 21.1% of women gave birth by cesarean globally. 12 Cesarean delivery rates varied among countries, with average rates ranging from 5% in Sub-Saharan Africa to 42.8% in Latin America and the Caribbean.Moreover, projections for 2030 are alarming.…”
mentioning
confidence: 99%